780 Quantitative cell-based bioassays to advance immunotherapy programs targeting immune checkpoint receptors. (9th November 2020) - Grailer, Jamison; Gilden, Julia; Stecha, Pete; Garvin, Denise; Wang, Jun; Beck, Michael; Hartnett, Jim; Krishnan, Gopal; Fan, Frank; Cong, Mei; Cheng, Zhi-Jie
Abstract : Background: The human immune system is comprised of a complex network of immune checkpoint receptors that are promising new immunotherapy targets for the treatment of a variety of cancers and autoimmune disorders. The Nobel prize for Medicine in 2018 was awarded for seminal studies on the role of immune checkpoint targets in T cell activation and furthermore, combining different strategies to release the brakes on the immune system with the aim of eliminating tumor cells even more efficiently. Immunotherapies designed to block co-inhibitory receptors (e.g. PD-1, CTLA-4, TIGIT) are showing unprecedented efficacy in the treatment of cancer. However, not all patients and tumor types respond to this approach. This has resulted in broadening of immunotherapy research programs to target additional co-inhibitory (e.g. LAG-3, TIM-3) and co-stimulatory (e.g. 4-1BB, GITR, OX40, ICOS) receptors individually and in combination. A major challenge in the development of antibody-based biologics is access to quantitative and reproducible functional bioassays. Existing methods rely on primary cells and measurement of complex functional endpoints. These assays are cumbersome, highly variable and fail to yield data required for drug development in a quality-controlled environment. Methods: To address the need of access to a robust and reliable functional assay for immunotherapy drug development programs, we have developed a suite of cell-based functional bioassays to interrogate modulation of immune checkpoint receptors individually (e.g. PD-1, CTLA-4, LAG-3, TIM-3, GITR, 4-1BB, OX40, CD40) and in combination (e.g. PD-1+CTLA-4, PD-1+4-1BB). These assays consist of stable cell lines that express luciferase reporters driven by response elements under the precise control of mechanistically relevant intracellular signals. Thus, the bioassays reflect mechanisms of action for the drug candidates designed for each immune checkpoint receptor and demonstrate high specificity, sensitivity and reproducibility. Here we describe the application of MoA-based immune checkpoint receptor bioassays as tools for biologics drug discovery, development, potency and stability studies. Results: We demonstrate that these bioassays measure response and inhibition with blocking drugs or potency changes from stressed samples. Conclusions: In summary, these reporter-based bioassays provide valuable tools for the development, stability testing, and potency determination in the manufacture of biologics that are targeted to immune checkpoint.